Analysis of Citizen's Charter Policy as A Strategy for Improving the Quality of Public Services in the Issuance of Driving License - Harianja, Marasi Kindly (Journal of Public Representative and Society Provision, 2023)
The service of driving licenses (SIM) is one of the public services of various other public services owned by the National Police. The state gives full authority to the Police to provide these services as stipulated in Law no. 22 of 2009 concerning Road Traffic and Transportation. The purpose of this study is to 1) analyze the issuance of SIMs at the Sorong Polres, 2) analyze the Citizen's Charter policy (service contract) as a strategy to improve the quality of public services in issuing SIMs at the Sorong Polres. This study uses a qualitative approach, using a case study research method. Data collection was carried out using interview techniques, observation and document review. This research was conducted in early September 2021 with a total of 15 respondents consisting of members of the Indonesian National Police and the public. The location of the research was carried out at the Sorong Police Station. From the results of the study it was concluded that the SIM issuance service at the Sorong Polres is still not optimally implemented for the community because the SIM issuance service at the Sorong Polres is still exclusive and elite capture, with a gap between service quality and cultural dimensions in the SIM issuance service at the Sorong Polres then a strategic policy formulation is needed to improve the quality of public services that are more excellent than the previous services. The advice given is to make fundamental improvements to the SIM issuance service at the Sorong Polres in order to improve the quality of service, build a good service culture, namely having dedication, integrity, discipline, honesty and trustworthiness in providing services to the community, using software that can be displayed directly on service room so that it can quickly find out what is the criticism and input from the community in service, on mobile SIM cars added to the product by issuing new SIMs, there is intense supervision from the Provos Polres Sorong to monitor service officers, and adopting a Citizen's Charter (service contract) compiled and designed between the Sorong Police and other stakeholders and the community.